Aesthetic Rhythm poetic image in the poems of Alhadirah Thubiani - Aldandan, Awwad Ahmad (Arab Journal for Sciences and Research Publishing, 2020)
This research aims to identify the phenomenon of rhythm in the poems of Alhadrh Thubiani, it has represented as a model of the poetry of Aljahilya poems, The study examined the occasional weights, psychological aspects, rhetorical and emotional colours, so that the researcher will focus on how to achieve rhythm in the poetic image, the research divided into sub-headings:  biography shining, Alhadirah poems in the eyes of critics and scholars, reading in Alhadirah poems.
Keywords: The aesthetics of reception; The aesthetics of the rhythm of the poetic image; significance; The structure; The poetic image; Al-Hadira Al-Dhibyani